“Flawless” data: How Big Tech is penetrating modern agriculture - Strömberg, Amos (Journal of Agriculture, Food Systems, and Community Development, 2023)
First paragraphs: In The Immaculate Conception of Data, Kelly Bronson plunges into an increasingly intricate web of precision farming, agribusiness, computerized models, data accumulation, and the current (d)evolution of modern food production. The ongoing attempt to marry traditional crop cultivation with computer science and artificial intelligence (AI) is a perplexing fusion of two very different worlds, which Bronson does an excellent job of critically analyzing. Tracing the power relations among the world’s largest Big Tech corporations, some of which seem to even be on the threshold of forming oligopolies (Howard, 2016), Bronson makes the case that the seemingly insatiable optimism around data and digitalization to a large extent stems from ideologically driven narratives, social imaginaries, and techno-progressivist, if not purely transhumanist, discourses. In nothing short of a rigorous critique, Bronson teases out the roots of the data hype and scrutinizes the rhetoric which companies employ to buttress a novel idea of how food should be grown and produced—namely, with cutting-edge robotics, drones, sensor technologies, and data analytics. . . .